Cancer Stigma in Non-patient Population Visiting B&B Hospital, Lalitpur, Nepal: A Descriptive Cross-sectional Study - Shrestha, Roshani; Shrestha, Gambhir; Paneru, Pragya (Asian Pacific Journal of Cancer Care, 2023)
Introduction: Research on various aspects of cancer, including stigma among cancer patients have received considerable interest in the recent years, but very few studies have studied cancer related stigma in healthy population. This study aimed to assess the situation of cancer stigma among the non-patient population. Methods: This cross-sectional study included 330 purposively selected non-patient population of age 18-45 years visiting B&B Hospital, Lalitpur, Nepal from March 2019 to August 2019. The data was collected from self-administered questionnaires. Caner stigma was measured with the validated Cancer Stigma Scale, which assesses six sub domains viz. severity, personal responsibility, awkwardness, avoidance, policy opposition and financial discrimination. Results: The highest score in Cancer Stigma Scale was found in the “severity”, while the lowest in the “policy opposition”. The policy opposition statements “More government funding should be spent on care and treatment of those with cancer” and “cancer patients should be given top priority” attracted the highest level of agreement (75.4 - 81.6%) followed by the statement about their comfort with cancer patients (59.5%), the acceptability for insurance companies to reconsider a policy once diagnosed with cancer (54.5%). A similar proportion felt getting cancer is to be prepared for death (38.5%) and a cancer patient is to be blamed for its condition (33.7%). Conclusions: Cancer stigma persists in Nepal with varying level in different domains of stigma.